2007
DOI: 10.1128/jb.01929-06
|View full text |Cite
|
Sign up to set email alerts
|

Human Body Temperature (37°C) Increases the Expression of Iron, Carbohydrate, and Amino Acid Utilization Genes in Escherichia coli K-12

Abstract: Using DNA microarrays, we identified 126 genes in Escherichia coli K-12 whose expression is increased at human body temperature (37°C) compared to growth at 23°C. Genes involved in the uptake and utilization of amino acids, carbohydrates, and iron dominated the list, supporting a model in which temperature serves as a host cue to increase expression of bacterial genes needed for growth. Using quantitative real-time PCR, we investigated the thermoregulatory response for representative genes in each of these thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
46
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 73 publications
(82 reference statements)
6
46
0
2
Order By: Relevance
“…Tempera-ture was one of the first environmental cues recognized to affect the expression of global regulatory cascades that redirect bacterial cells to form biofilms by upregulating production of curli and extracellular polysaccharides along with bacterial cell surface-associated proteins and nucleic acids (19,24,(30)(31)(32)(33)(34)(35)(36). The selective expression of desired sets of genes in response to temperature cues is a common theme among commensal and pathogenic bacterial species for conserving energy and ensuring their survival and persistence in a specific niche as well as transmission to a new host or locale (28,29,37). A recent study comparing the global gene expression profiles of E. coli K-12 grown at 37°C or 30°C showed elevated expression of metabolic pathways, such as uptake and utilization of amino acids, carbohydrates, and iron needed for rapid growth at 37°C (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tempera-ture was one of the first environmental cues recognized to affect the expression of global regulatory cascades that redirect bacterial cells to form biofilms by upregulating production of curli and extracellular polysaccharides along with bacterial cell surface-associated proteins and nucleic acids (19,24,(30)(31)(32)(33)(34)(35)(36). The selective expression of desired sets of genes in response to temperature cues is a common theme among commensal and pathogenic bacterial species for conserving energy and ensuring their survival and persistence in a specific niche as well as transmission to a new host or locale (28,29,37). A recent study comparing the global gene expression profiles of E. coli K-12 grown at 37°C or 30°C showed elevated expression of metabolic pathways, such as uptake and utilization of amino acids, carbohydrates, and iron needed for rapid growth at 37°C (29).…”
mentioning
confidence: 99%
“…For example, flagellar genes are expressed under conditions favoring rapid growth and expression of curli is enhanced during slow growth or stationary phase, nutritional deprivation, low temperature, low osmolarity, and oxidative stress (26)(27)(28)(29)(30). Tempera-ture was one of the first environmental cues recognized to affect the expression of global regulatory cascades that redirect bacterial cells to form biofilms by upregulating production of curli and extracellular polysaccharides along with bacterial cell surface-associated proteins and nucleic acids (19,24,(30)(31)(32)(33)(34)(35)(36).…”
mentioning
confidence: 99%
“…One aspect contributing to this mismatch was that the simple nature of these solutions was not appropriate as already discussed. Another aspect was that the temperature was below the human body temperature of 37°C [101]. This is significant as an increase in temperature is associated with increased chemical activity, due to the increase in kinetic energy that is afforded from the increased temperature.…”
Section: Temperaturementioning
confidence: 99%
“…Investigations into bacterial pathogenesis have revealed an intuitive connection between basic metabolic processes of adaptation and virulence. For example, it has been reported that bacteria alter the transcription of carbohydrate utilization genes and virulence factor-encoding genes in response to the sugar availability encountered in the environment, in particular, in the infected host (44,65,67,69,79). Consequently, regulatory mechanisms that connect carbohydrate metabolism to virulence factor production must have evolved.…”
mentioning
confidence: 99%